Tipos de cabeçadas e expressões faciais associadas ao estresse em cavalos sob trabalho leve - MARIA SIMARA PALERMO HERNANDES (2025)
The welfare of production animals has been increasingly recognized as an important indicator of sustainability, although it is still often neglected for working animals. This research was conducted to evaluate stress responses in horses subjected to light work using a headstall with a bit and a headstall without a bit (side pull). Chapter 1 presents the literature review, initially addressing the use of the bit in equitation, describing different types of bits and their impact on equine welfare. Then, alternatives to bit usage are explored, with an emphasis on bitless riding, in addition to discussing the main stress indicators in horses. Chapter 2 presents the article in which the physiological and behavioral stress responses of Pantaneiro horses subjected to light physical work were evaluated using two riding methods: a headstall with a snaffle bit and the side pull. Pantaneiro horses (n=5) were evaluated in a crossover design with two treatments: bit and side pull. Before the exercise, each animal was saddled and equipped with either a headstall with a bit or a side pull and led to the collection site, where it remained restrained for 5 minutes for physiological and facial parameter collection. Then, the horse was taken to the round pen and subjected to light physical exercise for 15 minutes. After the exercise, the animal returned to the collection site for another round of physiological and facial parameter measurements. The evaluated physiological parameters included surface body temperature (ocular, nasal, body, ear, and rectal), respiratory and heart rates, and heart rate variability through LF – Low Frequency, HF – High Frequency, and LF:HF – Low to High-Frequency Ratio. Facial expressions assessed included lip separation (AU25), jaw drop (AU26), increased eye white (AD1), tongue exposure (AD19), yawning (AD81), ears forward (EAD101), ear rotator (EAD104), nostril elevation (AUH13), blinking (AU145), half blink (AU47), and nostril dilation (AD38). The surface body temperature of horses using a bit was higher (p0.05). Heart and respiratory rates increased immediately after exercise for both treatments. LF, HF, and LF:HF were not influenced by treatments (p>0.05). Horses subjected to exercise using a bit showed a greater number of stress-related facial expressions, including AU25, AU26, AD19, AD81, and AU145. Facial expression AD38 was more prevalent immediately after exercise and five minutes post-exercise in the bit treatment. Horses subjected to light work with the side pull exhibited a lower frequency of stress-associated responses compared to those using a bit, demonstrating that the side pull is an effective tool for reducing stress in horses engaged in light work.